Primary malignant melanoma of the vagina: A case report - Giancarlo Sticca; Bojana Misheva; Herawaty Sebajang; Vanessa Samouelian; Rahima Jamal (Elsevier, 2023)
Malignant primary melanoma of the vagina (PMV) is a rare type of non-cutaneous melanoma often discovered in postmenopausal women. PMV has a very aggressive disease course and a poor prognosis. The best course of treatment is not presently agreed upon. In this report, we describe the case of a 68-year-old woman presenting with a malignant PMV and its subsequent management. The patient presented with right vaginal pain, abnormal vaginal bleeding and a new vaginal mass. A PET scan identified a 28 × 38 mm hypermetabolic vaginal lesion, without nodal involvement or distant metastasis. A posterior exenteration type 2B was performed, including the anal mucosa. Sentinel lymph node dissection, vaginal and rectal resection as well as a terminal colostomy were also carried out. Final staging was FIGO stage III and T4bN1. Four months later, the patient presented with a recurrent vaginal bleed and intra-vaginal induration. Imaging revealed loco-reginal recurrence at the site of the primary malignancy with countless metastases. The patient opted for palliative care given the early disseminated recurrence and her multiple comorbidities. We review the treatment options for PMV, mainly the importance of surgery as the mainstay of treatment as well as the interest of adding checkpoint inhibitor immunotherapy or targeted therapy to the treatment plan. We also summarize the characteristics of PMV and its main prognostic factors.